Corporate Social Responsibility (CSR) in the Travel Supply Chain: A Literature Review - Ibarnia-Caspistegui, Eneko; Garay, Lluis; Guevara-Plaza, Antonio (MDPI, 2020)
Traditional travel agencies and tour operators are recognized as relevant stakeholders in the tourism distribution chain, even though their role as transforming agents in the achievement of more sustainable tourism is beginning to be accepted. This study aims at reviewing the main topics and the most recent approaches from the academic literature in its analysis of corporate social responsibility (CSR) practices developed by these intermediaries. The work has been structured around six recurring themes in most of the studies carried out: the new intermediaries that operate on the Internet; the role of travel agencies and tour operators in tourism sustainability; the influence of the size of the company; CSR as a disruptive innovation in this sector; the potential of the sustainable tourism supply chain; and the motivations and attitudes of the managers of these businesses when they engage with responsibility. This last topic is developed in greater detail since it is closely linked to the previous ones and dictates, in most cases, the meaning and function of the sustainable performance. The conclusions show how tourism intermediaries have only just begun to develop CSR policies, and those that are committed to their implementation mostly opt for actions aimed at the environment.
Keywords: Agencias de viajes - Responsabilidad social; corporate social responsibility; sustainability; travel supply chain; tourism intermediares; large corporations; motivations